MOTIVASI SINGAPURA MERATIFIKASI ASEAN AGREEMENT ON TRANSBOUNDARY HAZE POLLUTION TAHUN 2003 - Firmayanti, Syahriani; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this research is to find out why Singapore ratified the ASEAN Agreement on Transboundary Haze Pollution (AATHP) in 2003. Forest fire became an agenda that happen almost every year in Southeast Asia, especially in Indonesia. It made Southeast Asia being covered by a haze during the fire occures, particularly Singapore. This research describes three things. First, what motivation which drives Singapore did ratify AATHP as a regional response in the fight against transboundary haze pollution under ASEAN. Second, the impact of transboundary haze pollution toward the whole life aspects in Singapore. Third, the condition of Singapore after ratification AATHP.This research theoretically has built with Pluralism as perspectives and The National State as the level of analysis in International Relations, and supported by Green Theory as well. The formulation of all arguments, facts, and theoretical framework in this research is guided by qualitative explanation methods. The technique of this research is the study of library. The collected data is gotten from journals, books, Thesis and website articles which related to the problems.This research noted that Singapore is a country that is highly vulnerable to the adverse effects of transboundary haze pollution, because haze potentially covered the entire surface area of Singapore. When this thing happened, all activities in societyis disrupted, safety is threatened, andthe impact on the economy of Singapore is quite significant. It encouraged Singapore to take a decisive stepby ratifying AATHP as a political response to overcome the transboundary haze problem. However, when AATHP was not run effectively, Singapore must take a more decisive action. Further, Singapore made a Transboundary Haze Pollution Act (THPA) which is designed to have an extraterritorial range and is expected to work effectively in addressing transboundary haze problem in Singapore.Keywords : Transboundary, Haze, Pollution, Singapore, Ratification, Impact